A rehabilitation programme focussing on pelvic floor muscle training for persistent lumbopelvic pain after childbirth: A randomized controlled trial - Hui Wang; Xiaolan Feng; Zishu Liu; Yan Liu; Ribo Xiong (Medical Journals Sweden, 2021)
Objective: To evaluate the effects of a rehabilitation programme for lumbopelvic pain after childbirth. Methods: Women with lumbopelvic pain 3 months postpartum were included in a randomized controlled trial. Patients in the intervention group (n = 48) received pelvic floor muscle training combined with neuromuscular electrical stimulation of the paraspinal muscles for 12 weeks, while patients in the control group (n = 48) received neuromuscular electrical stimulation for 12 weeks. Outcomes were measured with the Triple Numerical Pain Rating Scale (NPRS), Modified Oswestry Disability Questionnaire (MODQ) and Short-Form Health Survey-36 (SF-36). Results: The NPRS score was significantly better in the intervention group at 12 weeks compared with the control group (p = 0.000). The MODQ score was significantly better at 6 and 12 weeks compared with the control group (p = 0.009 and p = 0.015, respectively). The mean value of the Physical Components Summary of the SF-36, was significantly better in the intervention group at 6 weeks (p = 0.000) and 12 weeks (p = 0.000) compared with the control group, but there was no significant improvement in Mental Components Summary of the SF-36. Conclusion: A postpartum programme for women with lumbopelvic pain is feasible and improves the physical domain of quality of life.